Shaping Noble Character: The Impact of Islamic Religious Education on Student Morals at Junior High School - Euis Latipah; Ita Nurwita; Lia Amelia Z; Dede Fatimah (STAI Hubbulwathan Duri, 2025)
Islamic Religious Education (PAI) plays a significant role in shaping students' morals by instilling Islamic values, promoting good behavior, and fostering a religious school environment. This study aims to analyze the role of PAI in moral development and identify key factors that support its effectiveness. A qualitative descriptive method was employed using purposive sampling. Data were collected through observation, interviews, and documentation, followed by data reduction, presentation, and conclusion drawing to ensure a comprehensive analysis. Findings indicate that PAI contributes significantly to students’ moral development at SMP Yapip Pacet. Teachers serve not only as educators but also as role models in daily life. The success of moral education is influenced by the integration of classroom learning, school-wide practices, and collaboration between the school and family. The study highlights the importance of reinforcing teachers' roles, employing effective learning strategies, and fostering a supportive school environment. The synergy between education, habitual practices, and parental involvement enhances the internalization of Islamic values in students’ daily lives. PAI is essential in shaping students' character, requiring continuous strengthening through effective teaching, role modeling, and school-family collaboration. Future research should explore innovative approaches to further enhance moral education in different educational settings.